In Vitro Activities of Four Novel Triazoles against Scedosporium spp. - Carrillo, A. J. (American Society for Microbiology, 2001)
In order to develop new approaches to the treatment of the severe and usually fatal infections caused by Scedosporium spp., the in vitro antifungal activities of four novel triazoles (posaconazole, ravuconazole, voriconazole, and UR-9825) and some current antifungals (amphotericin B, ketoconazole, itraconazole, and nystatin) were determined. The latter group was clearly ineffective against the two species tested. The four new antifungals showed activity against Scedosporium apiospermum, and UR-9825 and voriconazole were active against S. prolificans.